Maternal mortality and morbidity burden in the Eastern Mediterranean region: findings from the Global Burden of Disease 2015 study - Khalil, Ibrahim; Bärnighausen, Till; Jonas, Jost B.; Mohammed, Shafiu (International journal of public health, 2017)
Assessing the burden of maternal mortality is important for tracking progress and identifying public health gaps. This paper provides an overview of the burden of maternal mortality in the Eastern Mediterranean Region (EMR) by underlying cause and age from 1990 to 2015.
Gesehen am 23.04.2020